Devolution of Power Plan 2000: A Case Study of Bahawalpur District - Dr. Razia Musarrat (Journal of Political Studies, 2008)
The local government system introduced in 2000 has its own impact on the provincial as well as the national political, administrative, social and economic structures. To establish a real, on-ground framework of this system and its impact on the district level administration, the following study has been organized to inquire and analyze this issue in its multidimensional aspects. This study provides a practical and analytical approach into the local government system and studies its impact as well as its post-implementation performance through the research focused on Bahawalpur District. Bahawalpur is one of the largest districts in the south of the Punjab with an area of 15,918 Square miles (Rizvi, 2007). Geographically, Bahawalpur has a significant location i.e., it is centrally located on the national highway leading from Khyber to Karachi. It is surrounded by River Sutluj in North and Cholistan (Desert) on the Eastern and Head Punjnad on the Western front. It shares its boundaries with Bahawalnagar, Rahim Yar Khan and Lodhran districts and serves as an important marketing centre for the surrounding areas. According to the census of 1998, the urban population is 665304 as compared to rural i.e. 1767787 (Adeeb, 2007) and almost 90 percent of the population is Muslim. The overall climate is dry and hot. The area enjoys an average annual rainfall of 200 mm. Saraiki is the local parlance of the area. Urdu and Punjabi are also spoken and understood by most of the people. A few hundred are Pashto, Sindhi and Balochi speaking (Adeeb, 2007). Historically speaking, the Nawab of Daudputra family Muhammad Bahawal Khan Abbasi founded the city in 1748 (Adeeb, 2007). It was formerly an Indian princely state capital. When West Pakistan was declared to be One Unit in 1955, Bahawalpur State was merged into it. Bahawalpur is known for its historical places e.g Noor Mahal, Gulzar Mahal Daulat Khana, Bahawal Garh Palace and Fort Derawar (Rehman,). It also boasts many reputable educational institutions, namely The Islamia University of Bahawalpur, Sadiq Public School and Quaid-e-Azam Medical College.